2013
DOI: 10.3382/ps.2012-02903
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Clostridium perfringens isolates from healthy turkeys and from turkeys with necrotic enteritis

Abstract: Clostridium perfringens is an important bacterial pathogen, especially in poultry, where it can lead to both subclinical and clinical disease. The aim of this study was to present data on pathological findings at outbreaks of necrotic enteritis (NE) in turkey production in Finland during the period from 1998 to 2012. Furthermore, C. perfringens isolates from healthy and diseased turkeys were characterized and their genetic diversity was investigated using pulsed-field gel electrophoresis (PFGE). Isolates (n = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 25 publications
4
26
0
Order By: Relevance
“…Recent studies have shown a high correlation between the detection of the NetB-encoding gene and the occurrence of NE in broiler chickens and in turkeys (KEYBURN et al, 2008;ALLAART et al, 2012;LYHS et al, 2013). In the present study, there were no C. perfringens strains positive for of the 18 Clostridium perfringens strains isolated from Ramphastidae, Tinamidae and Cracidae species in Brazil.…”
Section: Discussionmentioning
confidence: 42%
“…Recent studies have shown a high correlation between the detection of the NetB-encoding gene and the occurrence of NE in broiler chickens and in turkeys (KEYBURN et al, 2008;ALLAART et al, 2012;LYHS et al, 2013). In the present study, there were no C. perfringens strains positive for of the 18 Clostridium perfringens strains isolated from Ramphastidae, Tinamidae and Cracidae species in Brazil.…”
Section: Discussionmentioning
confidence: 42%
“…Both chickens and turkeys were from conventionally raised indoor flocks. The samples were collected on 14 different Danish chicken farms between 1997 and 2002 [12], and seven different Finnish turkey farms between 1997 and 2010 [8]. The samples were primarily from the intestine, but six chicken isolates were obtained from liver samples (Additional file 1).…”
Section: Main Textmentioning
confidence: 99%
“…Colonization of the intestine by netB -positive type A strains is known to be the main cause of necrotic enteritis (NE) in broilers [4, 5], which constitutes a considerable burden to the animal welfare and production yield in the international poultry industry [6]. NetB is essential in the pathogenesis of NE in chickens [4, 5], whereas the prevalence of netB is low among diseased turkeys [7, 8]. Few studies of the virulence gene content in strains from turkeys with NE and enteric diseases have been carried out [9] and to our knowledge, there are no reports on whole-genome sequencing of C. perfringens isolates from turkeys.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it was demonstrated that the NetB-encoding gene (netb) is common in C. perfringens type A isolates from NE birds, whereas it is rare in healthy birds (KEYBURN et al, 2008). A similar association was recently reported in turkeys: netb was identified in 6.6% of the C. perfringens strains isolated from turkeys with NE but in none of the strains isolated from healthy animals (LYHS et al, 2013). Because reports have indicated that C. perfringens netbnegative strains can cause NE, it appears that there are other virulence factors involved (LEE et al, 2011).…”
Section: Broiler Chickensmentioning
confidence: 54%